Hunger-strike in Andamans repression and resistance of transported prisoners - Kumar Pramod (Lucknow Martyrs Memorial and Freedom Struggle Research Centre, 2004)
This book reflects a well documented history of third hungertstrike by transported prisoners in cellular jail in which three participants had died during forced feeding.
Keywords: Andamans-history; India-history